Double sided assemblymline balancing problem by using comsoal : an automotive industry case study - Aishatul Fadhilah Ramzi (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This project will presents optimum efficiency improvement of assembly production line by applying line balancing technique in industry chosen. In order to obtain sustainability of optimum production, company must manage the production line very well. In this case, a systematic technique or approach should be introduced. One of the technique is line balancing technique. The used of line balancing technique was proved able to increase the productivity of the company. Several improvements steps will be suggessted throughout the project to current system such as rearranging the arrangement of the part eliminating unnecessary activities of the assembly process, reducing the cycle time and balancing manpower workload. This project is done at Motosikal dan Enjin Nasional (MODENAS).